ANALISIS PENDAPATAN USAHA KERAJINAN ROTAN DI KABUPATEN INDRAGIRI HULU (Studi Kasus di Desa Buluh Rampai Kecamatan Seberida Kabupaten Indragiri Hulu Provinsi Riau ) - Riswanti, Purwi; Sulaeman, Rudianda; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Rattan processing as Non Timber Forest Products (NTFPs) create a variety of production activities for various industries rattan craft. Indragiri Hulu District right in Buluh Rampai village is one of which has a very hight potential in the rattan craft industry. This research intend to analyze the magnitude of the cost, acceptance, the marketing of rattan craft and analyze efficiency of the rattan craft business. The population in this research is the rattan craft entrepreneur in Buluh Rampai Village. The method used in this research is using of the cencus method and data collection techniques used in this research is interviews and questionnaires. The result of this research showed that the analysis of rattan craft business in Buluh Rampai Village is 1. The amount of production costs incurred by rattan craftsmen per year is Rp85.517.209. 2. Gross revenue earned of craftsmen per year average amount Rp157.200.000. 3. Net revenue earned of craftsmen per year average amount Rp71.682.791. 4. Marketing channel of the rattan craft there are 2 channels 1) Producer-consumer 2) Producer-collectors-retailer-consumer. 5. Marketing costs of the rattan craft in Buluh Rampai Village isn’t expend costs, this is due the craftsmen directly sell to consumers 6. Results of the analysis of business efficiency that obtained the craftsmen in Buluh Rampai Village 1.83, therefore rattan craft business in Buluh Rampai Village economically feasible to be continued and developed.Keywords: Rattan, Rattan Craft, Costs Production, R/C ratio